Penerapan Certainty Factor dalam Diagnosa Penyakit Gigi dan Mulut Berbasis Web di Puskesmas Halilulik - Marselinda Kabu; Emerensiana Ngaga; Alfry Aristo Jansen Sinlae (JUKI : Jurnal Komputer dan Informatika, 2023)
Currently, information technology is growing rapidly in the world of medicine. This advancement is very helpful for doctors in finding information to diagnose dental and oral diseases in patients. In addition, advances in information technology also enable doctors to find new symptoms and diseases that have not been identified before. However, the teeth and mouth organs are often neglected by the people in Belu District, especially in West Tasifeto District, due to a lack of awareness of the importance of maintaining oral hygiene. In fact, dental and oral health is very important because they are vital organs that are connected to the rest of the body. Therefore, a web-based expert system application is needed that can help the community and health centers, especially Halilulik Health Center, diagnose dental and oral diseases. This study uses the certainty factor method, which can provide solutions that follow facts. This application was built using the PHP programming language and the MySQL database. In this research, an expert system has been successfully developed that can assist in diagnosing dental and oral diseases without having to wait for the arrival of a dental and oral specialist. The use of this expert system can assist the public in diagnosing dental and oral diseases and providing information about diseases and symptoms of the teeth so that they can avoid these diseases.